If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + 10) * 2 = (3x + -55) * 2 Reorder the terms: (10 + 2x) * 2 = (3x + -55) * 2 Reorder the terms for easier multiplication: 2(10 + 2x) = (3x + -55) * 2 (10 * 2 + 2x * 2) = (3x + -55) * 2 (20 + 4x) = (3x + -55) * 2 Reorder the terms: 20 + 4x = (-55 + 3x) * 2 Reorder the terms for easier multiplication: 20 + 4x = 2(-55 + 3x) 20 + 4x = (-55 * 2 + 3x * 2) 20 + 4x = (-110 + 6x) Solving 20 + 4x = -110 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 20 + 4x + -6x = -110 + 6x + -6x Combine like terms: 4x + -6x = -2x 20 + -2x = -110 + 6x + -6x Combine like terms: 6x + -6x = 0 20 + -2x = -110 + 0 20 + -2x = -110 Add '-20' to each side of the equation. 20 + -20 + -2x = -110 + -20 Combine like terms: 20 + -20 = 0 0 + -2x = -110 + -20 -2x = -110 + -20 Combine like terms: -110 + -20 = -130 -2x = -130 Divide each side by '-2'. x = 65 Simplifying x = 65
| -1+3.3h=-16 | | (8x)0(8x)= | | 50+6m= | | 9+x=-8x-18 | | X=50-46 | | (2x^3-2/7)^3 | | 3y+3+2y+6=10y-31 | | -9+3n=-63 | | g(n)=25-49(n-1) | | k/3=-16 | | ((2x^3-2/7))^3 | | -32=-17+x | | 99=9y | | -0.6u-9=-5 | | 2(3z-1)-2(4-2Z)=8 | | 13x-7=12x-12+x+5 | | -3/2y=22 | | 75-9n= | | p/14=1 | | -20=k-19 | | 10x-16=8x+7 | | -54=9h | | 4b+2=9b-23 | | 0.28y+8=11 | | 3(6x-5)=18x+15x | | b/17=-13 | | 4(x-30)+5x=-48 | | x+(1+x)+(2+x)=228 | | 5r-4r=16 | | -8(9h-5)=-17 | | -12+4n=4 | | -11+b=-3 |